Scottish surveys core questions, 2013 (UK Data Service, 2016)
The Scottish Surveys Core Questions (SSCQ) is an annual Official Statistics publication for Scotland. SSCQ provides reliable and detailed information on the composition, characteristics and attitudes of Scottish households and adults across a number of topic areas including equality characteristics, housing, employment and perceptions of health and crime. SSCQ gathers survey responses from identical questions in the Scottish Crime and Justice Survey, the Scottish Health Survey and the Scottish Household Survey into one output. The pooling of Core Questions results in an annual sample of around 21,000 respondents, providing unprecedented precision of estimates at national level. This sample size enables the detailed and reliable analysis of key national estimates by country of birth, ethnicity, sexual orientation, religion, age and sex, marital status, education level and economic activity, as well as tenure, car access and household type. SSCQ also enables a detailed sub-national analysis by Local Authority, urban-rural classification and Scottish Index of Multiple Deprivation.